Introduction: Special Issue of Philosophies on Forms of Life: The Future of the Concept - Juliet Floyd; Sandra Laugier (Philosophies)
Wittgenstein’s notion of “forms of life” has received recent attention in philosophy, political theory, anthropology, and the sociology and philosophy of new medias [...]